Metal bioaccumulation and precious metal refinery wastewater treatment by phoma glomerata,Bronwyn Moore Masters Thesis - Moore, Bronwyn Ann (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology)
The biosorption of copper, nickel, gold and platinum from single metal aqueous solutions by the nickel hyperaccumulator Berkheya coddii plant biomass was investigated. Potentiometric titrations of the biomass and determination of optimal sorption pH for each metal showed that nickel ions were released from the biomass into solution. The presence of free nickel ions interfered with the uptake of the other three metals and further biosorption investigations were discontinued. Three fungal isolates found colonising metal solutions were cultured and screened for their ability to remove 50 mg.lâ »Â¹ of copper, nickel, gold and platinum from solution and to survive and grow in precious metal refinery wastewaters. One isolate was selected for further studies based on its superior metal uptake capabilities (35 and 39 mg.lâ »Â¹ of gold and platinum, respectively) and was identified as Phoma glomerata. Copper, nickel, gold and platinum uptake studies revealed that nickel and gold were the most toxic metal ions, however, toxicity was dependent on pH. At pH 6 more biomass growth was achieved than at lower pH values and metal uptake increased by 51 and 17 % for copper and nickel, respectively. In addition, the production of extracellular polymeric substances played a role in base metal interaction. Precious metals were observed to be preferentially removed from solution, complete removal of gold and platinum was observed at all initial pH values, 89 % of copper was bioaccumulated at an initial metal concentration of 55 mg.lâ »Â¹ (pH 6) and only 23 % of nickel was removed from solution under the same conditions. Metal bioaccumulation was confirmed through transmission electron microscopy and micro particle induced X-ray emission. The effect of P. glomerata immobilised in a packed bed reactor on precious metal refinery wastewaters was investigated. It was found that the fungal isolate was not able to remove the high salt and chemical oxygen demand concentrations found in the wastewaters, however due to its ability to survive and grow in undiluted wastewater and remove metal ions from solution it may be utilised as a metal detoxification step in the treatment process train.,PDFCreator Version 0.9.0,AFPL Ghostscript 8.53
Keywords: Metals -- Bioaccumulation; Water purification -- South Africa; Metal ions; Water -- Purification -- Biological treatment -- South Africa; Water quality management -- South Africa; Factory and trade waste -- Purification -- South Africa; Metals -- Refining; Hyperaccumulator plants